pH-Metric Method for Ligand Dissociation Constants of Mercaptotriazoles and Their Reactions. - SARASWATHI, K.; SIVARAMA BABU, S.; SUNANDAMMA., Y. (Asian Journal of Chemistry, 2010)
The proton ligand dissociation constants, log KL of a few mercaptotriazoles and the stability constants of their complexes with bivalent metal ions have been determined using Bjerrum-Calvin pH titration technique as extended by Irving and Rossotti. The order of stability constants of metal complexes follows Irving-William series and the acid dissociation constant values of ligands are in the order L1 > L2 > L3 > L4·